Serious infections in children: an incidence study in family practice - Van Den Bruel, A; Bartholomeeusen, S; Aertgeerts, B; Truyers, C; Buntinx, F (BioMed Central, 2006)
Background: Information on the incidence of serious infections in children in general practice is scarce. However, estimates on the incidence of disease are important for several reasons, for example to assess the burden of disease or as a basis of diagnostic research. We therefore estimated the incidence of serious infections in general practice in Belgium. Methods: Intego is a morbidity registration network, in which 51 general practitioners continuously register all diagnoses and additional data in their electronic medical records. Serious infections were defined as pneumonia, sepsis, meningitis, pyelonephritis and osteomyelitis. Incidences are calculated for the period of 1998 to 2002, per 1000 patients in the yearly contact group, which is the group of patients that consulted their GP at least once that year, and in the practice population, which is the estimated true population of that practice. Results: The incidence of all infectious diseases peaks in children between 0 and 4 years, with 1731 infections per 1000 children per year in the yearly contact group. Incidence drops with increasing age: 972 infections per 1000 children per year in children between 5 and 9 years old, and 732 in children between 10 and 14 years old. The same decline in incidence is observed in the subgroup of serious infections: 21 infections per 1000 children per year in children between 0 and 4 years, 12 in children between 5 and 9 years and 5 in children between 10 and 14 years. The results for the estimated practice population are respectively 17, 9 and 4 serious infections per 1000 children per year. Conclusion: In contrast to the total incidence of acute infections, serious infections are rare, around 1% per year. Children younger than 4 years old have the highest risk for serious infections, and incidences of some infections are different for boys and girls.